Microfluidic/HPLC combination to study carnosine protective activity on challenged human microglia: Focus on oxidative stress and energy metabolism - Privitera, Anna; Cardaci, Vincenzo; Weerasekara, Dhanushka; Saab, Miriam Wissam; Diolosà, Lidia; Fidilio, Annamaria; Jolivet, Renaud Blaise; Lazzarino, Giuseppe; Amorini, Angela Maria; Camarda, Massimo; Lunte, Susan Marie; Caraci, Filippo; et al. (Frontiers in Pharmacology, 2023)
Carnosine (β-alanyl-L-histidine) is a naturally occurring endogenous peptide widely distributed in excitable tissues such as the brain. This dipeptide possesses well-demonstrated antioxidant, anti-inflammatory, and anti-aggregation properties, and it may be useful for treatment of pathologies characterized by oxidative stress and energy unbalance such as depression and Alzheimer’s disease (AD). Microglia, the brain-resident macrophages, are involved in different physiological brain activities such synaptic plasticity and neurogenesis, but their dysregulation has been linked to the pathogenesis of numerous diseases. In AD brain, the activation of microglia towards a pro-oxidant and pro-inflammatory phenotype has found in an early phase of cognitive decline, reason why new pharmacological targets related to microglia activation are of great importance to develop innovative therapeutic strategies. In particular, microglia represent a common model of LPS-induced activation to identify novel pharmacological targets for depression and AD and numerous studies have linked the impairment of energy metabolism, including ATP dyshomeostasis, to the onset of depressive episodes. In the present study, we ﬁrst investigated the toxic potential of LPS + ATP in absence or presence of carnosine. Our studies were carried out on human microglia (HMC3 cell line) in which LPS + ATP combination has shown the ability to promote cell death, oxidative stress, and inflammation. Additionally, to shed more light on the molecular mechanisms underlying the protective effect of carnosine, its ability to modulate ROS production and the variation of parameters representative of cellular energy metabolism was evaluated by microchip electrophoresis coupled to laser-induced fluorescence and high performance liquid chromatography, respectively. In our experimental conditions, carnosine completely prevented LPS + ATP-induced cell death and oxidative stress, also completely restoring basal energy metabolism in human HMC3 microglia. Our results suggest a therapeutic potential of carnosine as a new pharmacological tool in the context of multifactorial disorders characterize by neuroinflammatory phenomena including depression and AD.